The Incidence of Diagnosis of Munchausen Syndrome, Other Factitious Disorders, and Malingering - Harald Schrader; Thomas Bøhmer; Jan Aasly (Behavioural Neurology)
Background. Systematic studies on factitious disorders and malingering in large populations are rare. To address this issue, we performed a nationwide epidemiological study in Norway on the incidence of these diagnoses in an unselected patient population. In particular, we tried to confirm the diagnoses and to estimate the contribution of Munchausen syndrome to the spectrum of factitious disorders. Methods. We analyzed data obtained from the Norwegian Patient Registry (NPR), which provided a deidentified list of all patients from 2008 to 2016 who had received the ICD-10 diagnosis of F68.1 or the diagnosis code Z76.5. Results. Altogether, 237 patients (99 females; 138 males) received a diagnosis of F68.1. Code Z76.5 was applied to 52 patients (12 females; 40 males), all diagnosed within health institutions. Three of 1700 specialists (somatic specialist, psychologist, or psychiatrist) in private practice had diagnosed a factitious disorder in altogether 87 patients. After contacting these specialists, we could identify no true case of F68.1. For 24 of 146 patients who were equally distributed by gender within health institutions, we managed to identify the diagnosing healthcare providers. Of these 24 patients, only 11 correctly qualified for code F68.1. Only two female patients qualified for a Munchausen syndrome diagnosis. Conclusions. There is a male predominance for the diagnosis of malingering. An earlier suspicion of a female predominance for Munchausen syndrome is upheld. There is significant underdiagnosing and misdiagnosing for both conditions and for factitious disorders in general. To separate the most serious form of factitious disorders from milder forms and to facilitate more systematic research, we recommend a specific ICD diagnosis for Munchausen syndrome.